Compassion Culture of Javanese Adolescents in Yogyakarta - Setiani, Ismarini Bekti; Suwarjo, Suwarjo; Wangid, Muhammad Nur; Nurmalasari, Yuli; Jaya, Ahmad Chandra; Siregar, Syaninda Putri Asyifa (Yayasan Keluarga Guru Mandiri, 2025)
The background of this research focuses on the culture of compassion, which includes feelings of affection, empathy and concern for others, especially in helping or alleviating their suffering. This culture includes genuine concern and action for the well-being of others without expecting anything in return. The purpose of this study is to understand and analyze the extent to which the culture of compassion is applied by Javanese adolescents in Yogyakarta. This study used a quantitative approach with quantitative descriptive research methodology, where the sample taken consisted of 150 students. The results showed that most Javanese adolescents in the Yogyakarta have a high level of compassion culture, with 57% showing a strong empathetic attitude. A total of 33% showed a moderate level of affection culture, and 10% showed a low level. The conclusion of this study is that most adolescents in this area still maintain high values regarding affection, although there are differences in the level of application of this culture which is influenced by family factors, education, and the influence of technology. The contribution of this study is to provide insight into the culture of affection among adolescents and the factors that influence its implementation.